Vilém Flusser und der Paradigmenwechsel zur Internetkultur - Scherber, Peter (Slavistična revija, 2017)
Vilém Flusser (1920-1991) is known as one of the most important media theoreticians after Marshall McLuhan. As a kind of cosmopolitan scholar he worked in numerous media-related fields and other studies (i.e., philosophy, linguistics, photography and film, education, information studies, telematics, anthropology and so forth). Flusser's work is located, so to speak, at an extreme edge of the "Gutenberg Galaxy"; he tried to point out paths beyond its borders. Although he died in the early 1990s, he developed some interesting visions about the nascent new age of the internet and mobile computing.
Keywords: Flusser, Vilém, 1920-1991; informacijska družba; književnost; komunikacija; literature; medmrežje; pisanje; writing